Psychological Impact of Childhood Trauma on Adolescents: A Scoping Review - Mei Putri Crismayanti; Meidiana Dwidiyanti; Anggorowati Anggorowati (Indonesian Journal of Global Health Research, 2025)
Violence experienced in childhood will lead to a period of crisis when a person is in adolescence. The crisis period that arises is unique to adolescence. Some adolescents become increasingly experiencing crises or problems when in childhood they experience an unpleasant event or even trauma. Traumatic experiences in childhood will have their own impact on adolescents. Objektive: This study aims to get a clear picture of the psychological impact of childhood trauma on adolescents. Methods: Researchers use the scoping review method. The literature search was conducted using the search keywords "adolescents" AND "psychological" AND "childhood" AND "trauma". The databases used were Sciencedirect, Scopus, and Pubmed. Inclusion criteria were articles reviewed from publications within the last 5 years (2019-2023), articles that were in English, quantitative and/or qualitative research with a study population of former adolescents who experienced childhood trauma, and the full article was accessible. Stepwise screening was conducted and documented according to the PRISMA flowchart. Results: Based on identification, there were 463 articles from search engines from sciencedirect, scopus, and pubmed. The final results obtained were 6 articles that fit the criteria after going through the selection process. Childhood trauma has psychological effects that can arise such as the impact of mental distress at risk of suicide, the impact of suicide, psychosis (mental disorders), psychiatric disorders in offspring, borderline personality disorder and the impact on internet addiction. Researchers used the PEO (population, exposure, outcome) question format to find related research articles. Conclusion: Based on the analysis of the 6 literatures that have been reviewed, it can be concluded that the incidence of childhood trauma in adolescents will have a psychological impact.